THE EFFECT OF ACCOUNTING KNOWLEDGE, BUSINESS EXPERIENCE, EDUCATION LEVEL, AND BUSINESS SCALE ON THE USE OF ACCOUNTING INFORMATION SYSTEMS BY MSMES - Wahyuni; Mukminati Ridwan; Nasrullah (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2025)
This study analyzes the influence of accounting knowledge, business experience, educational level, and business scale on the use of Accounting Information Systems (AIS) in MSMEs in Gowa Regency. Using quantitative methods with multiple linear regression analysis, the results show that, both partially and simultaneously, these four variables have a positive and significant effect on AIS use. These findings confirm that increasing human resource capacity and business operational scale are key drivers in accelerating the adoption of financial technology. Synergy between individual competencies and systematic business needs is needed to realize more transparent and accountable financial management.